2020
DOI: 10.1061/(asce)gm.1943-5622.0001552
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Discrete-Element Modeling of Geocell-Reinforced Ballast Considering Breakage

Abstract: This paper presents a 3-dimensional discrete element modeling (DEM) study examining the settlement and breakage behavior of geocell-reinforced ballast.The reinforced ballast chamber reproduces the geocell in configuration and the ballast particles in shape and breakage characteristics. The reinforced ballast chamber is subjected to monotonic and cyclic loads. Parametric studies are conducted on the geocell embedment depth and ballast shape. For each case, ballast settlement, geocell responses and ballast break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Despite its considerable potential, the utilization of 3D cellular inclusions in railway tracks remains limited because of a lack of available methods for evaluating the extent of improvement offered by these inclusions. Consequently, several researchers have explored different techniques, such as FE and discrete element (DE) analyses, to evaluate the effectiveness of using cellular inclusions in enhancing the long-term stability of railway tracks [69][70][71][72][73]. However, the DE and FE methods require substantial computational This section examined the sustainable application of a geogrid in a GRPS railway embankment, highlighting its influence on the load transfer mechanism within the embankment fill.…”
Section: Generalmentioning
confidence: 99%
“…Despite its considerable potential, the utilization of 3D cellular inclusions in railway tracks remains limited because of a lack of available methods for evaluating the extent of improvement offered by these inclusions. Consequently, several researchers have explored different techniques, such as FE and discrete element (DE) analyses, to evaluate the effectiveness of using cellular inclusions in enhancing the long-term stability of railway tracks [69][70][71][72][73]. However, the DE and FE methods require substantial computational This section examined the sustainable application of a geogrid in a GRPS railway embankment, highlighting its influence on the load transfer mechanism within the embankment fill.…”
Section: Generalmentioning
confidence: 99%
“…The cell walls, junctions and the infills integrate into a thick engineered mattress of enhanced rigidity which as a system increases resilience of ground. The advantages have promoted deployment of geocell in a wide range of applications, e.g., foundations and embankments [1][2][3], earth retentions [4], utility pipeline overlying [5], railways sub-tracks [6,7], plate anchors [8], river banks [9] and vibration isolation beds [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mehdipour's research [17] indicated that geocells can disperse stress during the process of transmission by absorbing the load, which in turn reduces both permanent transverse and longitudinal deformation. Hegde, A. et al [18] and Liu, Y. et al [19] proposed a method for building three-dimensional (3D) geocell models. Dash, S.K.…”
Section: Introductionmentioning
confidence: 99%